2014
DOI: 10.1002/pen.23853
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state polymerization of poly(ethylene terephthalate): Effect of organoclay concentration

Abstract: Poly(ethylene terephthalate) (PET)/Cloisite 30B (C30B) nanocomposites of different organoclay concentrations were prepared using a water-assisted extrusion process. The reduction of the molecular weight (M w ) of the PET matrix, caused by hydrolysis during water-assisted extrusion, was compensated by subsequent solid-state polymerization (SSP). Viscometry, titration, rheological, and dynamic scanning calorimetry measurements were used to analyze the samples from SSP. The weight-average molecular weight (M w ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In some cases, such as in the addition of SiO 2 nanoparticles, an accelerating effect was observed attributed to the surface reactive groups that participate in reactions taking place during SSP . However, the existence of nanoclays in PET matrix was found to delay the molecular weight increase during SSP . The solid‐state reaction for such nanocomposites was found to progress at a slower rate compared to the unfilled PET, because of the improved gas‐barrier properties that this type of nanoparticle induces to the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, such as in the addition of SiO 2 nanoparticles, an accelerating effect was observed attributed to the surface reactive groups that participate in reactions taking place during SSP . However, the existence of nanoclays in PET matrix was found to delay the molecular weight increase during SSP . The solid‐state reaction for such nanocomposites was found to progress at a slower rate compared to the unfilled PET, because of the improved gas‐barrier properties that this type of nanoparticle induces to the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The loss angle (δ) was quite sensitive to the topological structure of the polymer matrix. As shown in Figure c, for all of the nanocomposites, δ < 90° over the entire frequency range, signifying the existence of long-chain branching. , It was confirmed that the chain extension/branching reactions took place for all C30B contents.…”
Section: Resultsmentioning
confidence: 53%
“…The shear-thinning behavior was observed for all nanocomposites, which could be explained by the entanglements associated with long-chain branching and/or the polymer−particle network-like structure. 21, 22 The storage modulus as a direct indicator of melt elasticity also varied with the molecular weight of nanocomposites. It was inferred that the enhancement of viscoelastic properties from the welldispersed clays was almost covered by that from the increase of molecular weight for the PET/PMDA/clay ternary system.…”
Section: Methodsmentioning
confidence: 99%
“…This is an important reason for the use of modified clay as two-dimensional platelet nanofiller in polymer composites (Hasegawa et al, 2000;Pettarin et al, 2008). One of the growing areas of PET usage is food and beverage packaging, where more applications are possible with improvement in PET's barrier performance to oxygen and carbon dioxide, and a decrease in weight of the final products (Dini et al, 2014a). One of the growing areas of PET usage is food and beverage packaging, where more applications are possible with improvement in PET's barrier performance to oxygen and carbon dioxide, and a decrease in weight of the final products (Dini et al, 2014a).…”
Section: Pet/nanoclaysmentioning
confidence: 99%